2012
DOI: 10.2116/analsci.28.613
|View full text |Cite
|
Sign up to set email alerts
|

Light Scattering: a Novel Approach to Analyze Protein 4.1R FERM Domain Interaction with Inside-out-vesicles in Solution

Abstract: In this study, we describe a novel application for light scattering, a method widely used for separation of molecules in solution based on their size. We demonstrate that light scattering analysis can monitor the change in particle size of protein 4.1R prior to and after binding to red blood cell inside-out-vesicles in solution. Light scattering constitutes therefore a novel tool to analyze protein-binding association constants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Because of recent improvements in instrument sensitivity, even proteins that produce weak light scattering intensity can be studied using DLS measurements [13][14]. Furthermore, the polydispersity obtained from DLS measurement is often used as a parameter for predicting protein crystal formation [15][16], indicating that DLS measurements can be adapted to study amyloid fibril formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of recent improvements in instrument sensitivity, even proteins that produce weak light scattering intensity can be studied using DLS measurements [13][14]. Furthermore, the polydispersity obtained from DLS measurement is often used as a parameter for predicting protein crystal formation [15][16], indicating that DLS measurements can be adapted to study amyloid fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…DLS, a technique used to measure protein diffusion due to Brownian motion, was used to evaluate amyloid fibril formation via the change in hydrodynamic diameter that accompanies fibril extension or unfolding in the presence of denaturants such as urea [8][9][10][11][12]. Because of recent improvements in instrument sensitivity, even proteins that produce weak light scattering intensity can be studied using DLS measurements [13][14]. Furthermore, the polydispersity obtained from DLS measurement is often used as a parameter for predicting protein crystal formation [15][16], indicating that DLS measurements can be adapted to study amyloid fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that DLS can be used to evaluate proteins, even those yielding weak light scattering intensities [7,8]. In addition, the polydispersity determined using DLS analysis is often used as a parameter for predicting the formation of protein crystals.…”
Section: Introductionmentioning
confidence: 99%